PENGARUH DUE PROFESSIONAL CARE DAN AKUNTABILITAS TERHADAP KUALITAS AUDIT DENGAN ETIKA AUDITOR SEBAGAI VARIABEL MODERASI (STUDI EMPIRIS PADA KANTOR AKUNTAN PUBLIK DI WILAYAH KOTA BEKASI DAN DKI JAKARTA) - Sayidaturrachmah, Chaerunnisa; Maidani, Maidani; Eprianto, Idel (SENTRI: Jurnal Riset Ilmiah, 2024)
Audit quality is a combination of a systematic audit process in accordance with generally accepted standards, with high-quality professional judgment used by competent and independent auditors to produce high-quality audits. High audit quality means that the auditor has carried out the audit with good due professional care and accountability, guided by full auditor ethics. On the other hand, low audit quality means that the level of due professional care and accountability of the auditor is low and they have not fully implemented ethics. This research aims to measure the influence of due professional care and accountability on audit quality with auditor ethics as a moderating variable. The approach used is quantitative. The data collection technique uses a survey method through a questionnaire instrument distributed to 100 auditors who work at 5 Public Accounting Firms in the Bekasi City area and 5 Public Accounting Firms in the DKI Jakarta area. Sampling was carried out using the purposive sampling method. Distribution of questionnaires starts from November 2023 to December 2023. Measuring tools to test research hypotheses use partial tests (t tests) and Moderated Regression Analysis (MRA) with statistical test tools using the Statistical Package for Social Science version 26 (SPSS 26). The research results show that partially due professional care and accountability have a positive effect on audit quality. On the other hand, the research results show that auditor ethics is unable to moderate the influence of due professional care and accountability on audit quality.